Cavernous lymphangioma: Two case reports - Cynthia Sargunam; Jayakar Thomas; P K Raneesha (Indian Dermatology Online Journal, 2013)
Lymphangiomas are congenital malformation of the lymphatic system that involve the skin and subcutaneous tissues. We are reporting two cases of cavernous lymphangioma. These cases are presented for their rarity.